Conceptions of competency: a phenomenographic investigation of beginning teachers in Malaysia - Goh, Pauline Swee Choo (Qualitative report, 2013)
I use phenomenography, which is an interpretive research approach, to seek and to discover what beginning teachers in Malaysia conceive and understand as competence in relation to what they do everyday as teachers. Phenomenographic approach is used because of its potential to capture variation of understanding, or way of constituting, the conceptions of competency. The outcomes of this study, therefore, are: (a) Categories of description which capture the critical dimensions of how beginning teachers in Malaysia understand the conceptions of competency, and, (b) An outcome space that describes the relationships between the categories. The results show that beginning teachers' conceptions of competence fall into five qualitatively different categories: (a) Classroom and Behaviour Management, (b) Knowing Subject Matter, (c) Understanding Students; (d) Reaching out for Assistance and Support, and (e) Possessing Values of Professionalism. The relationships between these categories are represented diagrammatically as the outcome space. The empirical data through phenomenography has provided a platform for teachers and teacher educators to ask: (a) "What are the implications, for beginning teachers, of their differing ways of understanding the conceptions of competency" (b) "How can teaching institutions better prepare pre-service teachers for their early years of teaching," and, (c) "How can appraisers (e.g., Principals, Head Teachers, Course Coordinators) use the outcomes to better plan any evaluations of competency?" I discuss each question in the article. Keywords: Malaysia, Beginning teachers, Conceptions of Competency, Competency, Standards, Phenomenography, Outcome Space, Teacher Educators